Extraordinary Carbon Fluxes on the Shallow Pacific Arctic Shelf During a Remarkably Warm and Low Sea Ice Period - O’Daly, Stephanie H.; Danielson, Seth L.; Hardy, Sarah M.; Hopcroft, Russell R.; Lalande, Catherine; Stockwell, Dean A.; McDonnell, Andrew M. P. (Frontiers in Marine Science, 2020)
The shallow Pacific Arctic shelf has historically acted as an effective carbon sink, characterized by tight benthic pelagic coupling. However, the strength of the biological carbon pump in the Arctic has been predicted to weaken with climate change due to increased duration of the open-water period for primary production, enhanced nutrient limitation, and increased pelagic heterotrophy. In order and gain insights into how the biological carbon pump is functioning under the recent conditions of extreme warming and sea ice loss on the Pacific Arctic shelf, we measured sinking particulate organic carbon (POC) fluxes from drifting and moored sediment traps, as well as rates of primary production and particle-associated microbial respiration in June 2018. We measured high sinking POC fluxes similar to and/or higher than previous measurements from this region (up to 2.3 g C m-2 d-1), reaching flux levels among the highest ever documented in the global oceans. Furthermore, high export ratios averaging 82% and low rates of particle-associated microbial respiration also indicated negligible recycling of sinking POC in the water column during spring of 2018. These results highlight the extraordinary strength of biological carbon pump on the Pacific Arctic shelf during an unusually warm and low-sea ice year. While additional measurements and time are needed to confirm the ultimate trajectory of these fluxes in response to ongoing climate change, these results call into question the prevailing hypothesis that the strength of the biological carbon pump in the Pacific Arctic will weaken under these conditions.